SIKAP DAN KEPUASAN RUMAH TANGGA KONSUMEN TEH CELUP SARIWANGI DAN SOSRO DI BANDAR LAMPUNG - Fitria Meriza; Dyah Aring Hepiana Lestari; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This study purposed to analyze the comparison consumer’s attitudes of Sariwangi and Sosro teabag to upper and lower middle class households, and the relationship between consumer’s attitudes and satisfaction of Sariwangi and Sosro teabag to households income. This study was conducted in RT 12 Sukarame Baru Village of Sukarame District and RT 07 Beringin Raya Village of Kemiling District, Bandar Lampung City. Total respondents are 60 households that consist of 30 respondents of consumers Sariwangi teabag and 30 consumers Sosro teabag. Sampling technique were using a simple cluster sampling and quota sampling. Data was taken on September until November 2014. Data was using qualitative and quantitative analysis. The results showed that the consumer’s attitudes of Sariwangi teabag are better than Sosro teabag, the consumer’s satisfaction of Sariwangi teabag are higher than Sosro teabag, and there is relationship between consumer’s attitudes and satisfaction of Sariwangi and Sosro teabag to households income. Key words : Sariwangi teabag, Sosro teabag, attitudes, satisfaction